Hubungan Aktivitas Fisik dengan Diabetik Neuropati Perifer pada Pasien DM Tipe 2 di Wilayah Kerja Puskesmas Abiansemal II Tahun 2019 - I Dewa Putu Gede Putra Yasa; I Kadek Oki Wanjaya; VM Endang SP Rahayu; I Gusti Ayu Ari Rasdini (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2020)
Type 2 diabetes mellitus (DM) occurs due to insulin resistance which causes high blood glucose and if it continues to be uncontrolled it can cause several complications, one of which is diabetic peripheral neuropathy. The effort that can be done is by changing lifestyle by increasing physical activity. The purpose of this study was to determine the correlation of physical activity with diabetic peripheral neuropathy. the type of research used is correlational research with a cross sectional design. The study was conducted at the Abiansemal II Community Health Center with 78 respondents selected by consecutive sampling. Diabetic variable peripheral neuropathy was measured by the DNS questionnaire and physical activity variables using the IPAQ questionnaire. The results showed 40 respondents (51.3%) were male with an average age of 62.8 years and 53 respondents (67.9%) were still working. The highest level of physical activity is at the moderate level of activity as much as 58 respondents (74.4%), low activity as many as 15 respondents (19.2%) and 50 respondents (64.1%) experience diabetic peripheral neuropathy. hypothesis testing using the chi square test with a p value of 0.022 (α = 0.05). It was concluded that there was a significant relationship between physical activity and diabetes peripheral neuropathy.